Pick - Hanan Khamis Alsharqawi (Journal of International Conference Proceedings (JICP), 2019)
PICK is a private organization which serves readymade, freshly prepared “BALANCED” food that’s good for all type of diets, whether you are on weight-loss, or weight-gain or even weight maintaining. They make sure that each item displayed at their shops has full nutritional information, this allows any customer to pick whatever he or she needs for any meal throughout the whole day.